The Effect of the Discovery Learning Model on The Understanding Concept of Fasting and Character of Piety in Junior High School Students - Mulikhah, Siti; Triwahyuni, Eges; Emyus, Ahmad Zaki (International Journal of Social Learning (IJSL), 2025)
This research is motivated by the fact that students understand fasting only as a ritual of worship without understanding the deep meaning and implications in everyday life, so that more interactive learning innovations are needed and motivate students to seek and find knowledge independently and actively, one of which is the discovery learning model. The purpose of this study was to determine whether there is a significant influence of Discovery Learning on students' understanding of the concept of fasting and whether there is a significant influence on students' character. This study uses a quasi-experiment type with a Pretest-Posttest with a Nonequivalent Control Group Design. The research sample was grade VIII junior high school students. Data collection techniques, tests, and questionnaires. It was concluded that discovery learning has significantly influenced students' understanding of fasting and the development of students' character.